Analisis Pergerakan Lereng Tambang Menggunakan Alat CHCNAV PS 2000 di PT Insani Bara Perkasa Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Muhammad Iksan Hamsyah; Revia Oktaviani; Lucia Litha Respati; Tommy Trides; Agus Winarno (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Mine slopes play a crucial role in ensuring the safety and sustainability of mining activities. Continuous mining operations can alter slope conditions, thereby increasing the potential for instability and slope failures. Slope stability is influenced by the balance between resisting forces and driving forces acting on the rock mass. When the resisting forces are smaller than the driving forces, the slope becomes unstable and failure may occur. Therefore, slope stability analysis is essential to prevent landslide hazards, as it directly affects occupational safety, equipment security, other assets, and overall production continuity. These conditions have encouraged PT Insani Bara Perkasa to develop a more accurate and real-time slope monitoring system. The application of radar-based monitoring was initiated using the CHCNAV PS-2000 system. This study aims to analyze the deformation behavior of mine slopes using radar technology. Data acquisition was conducted at Pit K1 Mahakam, PT Insani Bara Perkasa, covering Area 1 South, AR 2 South, AR 3 South, AR 5 South, AR 6 South, AR 7 West, AR 8 West, AR 9 South, AR 13 South, as well as TA-2, TA-3, and TA-6 areas. The study was carried out from November 2025 to December 2026. The analysis results indicate that most monitoring points are in stable conditions, with indications of a progressive phase observed in the AR 6 South area.